A dosimetry procedure for organs-at-risk in 177Lu peptide receptor radionuclide therapy of patients with neuroendocrine tumours. (December 2018) - Marin, Gwennaëlle; Vanderlinden, Bruno; Karfis, Ioannis; Guiot, Thomas; Wimana, Zena; Reynaert, Nick; Vandenberghe, Stefaan; Flamen, Patrick
Graphical abstract: Highlights: A dosimetry procedure for 177 Lu-DOTATATE is proposed. 177 Lu-DOTATATE dosimetry is feasible in clinical routine and repeatable. Standard dosimetry will lead to personalized therapy and improved outcome. Abstract: Purpose: Peptide receptor radionuclide therapy with 177 Lu-DOTATATE has become a standard treatment modality in neuroendocrine tumours (NETs). No consensus has yet been reached however regarding the absorbed dose threshold for lesion response, the absorbed dose limit to organs-at-risk, and the optimal fractionation and activity to be administered. This is partly due to a lack of uniform and comparable dosimetry protocols. The present article details the development of an organ-at-risk dosimetry procedure, which could be implemented and used routinely in a clinical context. Methods: Forty-seven patients with NETs underwent 177 Lu-DOTATATE therapy. Three SPECT/CT images were acquired at 4, 24 and 144–192 h post-injection. Three blood samples were obtained together with the SPECT/CT acquisitions and 2 additional samples were obtained around 30 min and 1 h post-injection. A bi-exponential fit was used to compute the source organ time-integrated activity coefficients. Coefficients were introduced into OLINDA/EXM software to compute organ-at-risk absorbed doses. Median values for all patients were computed for absorbed dose coefficient D / A 0 and for late effective half-life T 1 / 2 e f f for kidneys, spleen and red marrow. Results: Dosimetry resulted in a median[interquartile range] of 0.78[0.35], 1.07[0.58] and 0.028[0.010] Gy/GBq for D / A 0 and of 55[9], 71[9] and 52[18] h for T 1 / 2 e f f for kidneys, spleen and red marrow respectively. Conclusions: A dosimetry procedure for organs-at-risk in 177 Lu-DOTATATE therapy based on serial SPECT/CT images and blood samples can be implemented routinely in a clinical context with limited patient burden. The results obtained were in accordance with those of other centres.